Implementasi Metode Promethee untuk Diagnosis Penyakit Parasit pada Kambing (Studi Kasus : UPTD. Pembibitan Ternak dan Hijauan Makanan Ternak Kec. Singosari Malang) - Ade Wicaksono; Nurul Hidayat; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The goat is farm animals which have many uses and benefits, besides as a producer of meat, other products can also be utilized in accordance commodities generated by goats. On the practice field for livestock farming goats have many experience problems, one of problem which arises is in term of the endurance of the goat against parasities. Based on case occurs, tha system is built on this reaserch is “Implementation promethee method to diagnose parasities disease on goats (case study: UPTD. Livestock breeding and forage feed of kec. Singosari Malang). The method use to range the disease diagnose on goats employs promethee method; it counts the variable based on Multi Criteria Decision Making (MCDM). The result of the rank is based on the selection of the system. Therefore, the present result shows the similarity with the labor results while the rest does not show the same pattern. The testing of the system uses disease data taken form 50 samples of goats whose rate is divided according to worm group; scabies and myasis. Based on the experiment, the accuracy of the final result is close to 85%.